ACEH CULTURAL HERITAGE BASED ON CANTENGAN TRADITIONAL MEDICINE: AN EDUCATIONAL APPROACH TO ELEMENTARY SCHOOL STUDENTS - Musdiani; Siti Mayang Sari; Rahmatullah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses a descriptive qualitative method with a case study research model. Through the Tridharma service activity, researchers explain the phenomena that occur in society today, especially people who have compromised foot health. An ingrown toenail is a condition where the nail at the edge grows into the skin, causing the skin and underlying tissue to become inflamed. Ingrown toenails can occur on the nails of the hands and feet, but most often occur on the big toes. This research provides a real solution to educate elementary school students in recognizing and understanding traditional medicine that is effective and effective in dealing with this disease. Based on the fact that people still do not understand the meaning of traditional medicines inherited from the ancestors of the Indonesian people. In essence, all plants have their own benefits and functions. Students are given an understanding of how to make and use it to care for toenails to prevent ingrown toenails.